Family communication amongst conventional Malay man - Jamiah Manap,; Suzana Mohd Hoesni,; Mohd Rezal Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Communication is an essential tool for successful family functioning. Communication in the family is very important as it allows members to express their needs, wants, concerns and loves. Effective communication creates an atmosphere that allows family members to express their differences as well as love and admiration for one another. Love is the basis of happy and successful family. Each culture has their own way of expressing their love. Thus, the present research aimed to understand on how the conventional Malay men communicate their love in the family. A grounded theory approach in qualitative research design was used to answer the research question. The data collection involved semi-structured interview, observation and document analysis. As a result, seven main themes emerged. The themes are academic supervisor, personal advisor, financial provider, educator, positive role model, discipline maintainer, and spiritual leader. In summary, the conventional Malay Men communicate their love via a high commitment to the family especially to their children. As a result, the children appreciate their father’s love and make it as a reason to be successful in life. Good communication helps family members come to an understanding, which is the basis for all healthy familial relationships. Communication is a key way to show our family members how to love each other.